2022
DOI: 10.3390/curroncol29020055
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomal microRNAs as Predictive Biomarkers of Neoadjuvant Chemotherapy Response in Breast Cancer

Abstract: Background: Neoadjuvant chemotherapy (NACT) is an increasingly used approach for treatment of breast cancer. The pathological complete response (pCR) is considered a good predictor of disease-specific survival. This study investigated whether circulating exosomal microRNAs could predict pCR in breast cancer patients treated with NACT. Method: Plasma samples of 20 breast cancer patients treated with NACT were collected prior to and after the first cycle. RNA sequencing was used to determine microRNA profiling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Exosomes carry tumor-specific cargoes and are very stable in the fluids circulating within the human body; therefore, as shown in Table 2 , the detection of tumor exosomes is of significance for early diagnosis, evaluation of therapeutic efficacy, and prediction of treatment outcomes for cancer ( Zhao et al, 2021 ). The results of Todorova et al, support previous reports in which plasma serves as a source of Exo-miRNA biomarkers in TNBC ( Todorova et al, 2022 ). Zhong et al showed that exosomal lncH19 was associated with poor clinical results in the serum of breast cancer patients, including positive lymph node metastasis and positive distant metastasis ( Zhong et al, 2020 ).…”
Section: Clinical Application Potential and Limitations Of Exosomes I...supporting
confidence: 86%
“…Exosomes carry tumor-specific cargoes and are very stable in the fluids circulating within the human body; therefore, as shown in Table 2 , the detection of tumor exosomes is of significance for early diagnosis, evaluation of therapeutic efficacy, and prediction of treatment outcomes for cancer ( Zhao et al, 2021 ). The results of Todorova et al, support previous reports in which plasma serves as a source of Exo-miRNA biomarkers in TNBC ( Todorova et al, 2022 ). Zhong et al showed that exosomal lncH19 was associated with poor clinical results in the serum of breast cancer patients, including positive lymph node metastasis and positive distant metastasis ( Zhong et al, 2020 ).…”
Section: Clinical Application Potential and Limitations Of Exosomes I...supporting
confidence: 86%
“…Two sEVs miRNAs, miR-328-3p and miR-34a-5p that have been previously reported as predictive biomarkers of NAT response in BC [ 30 ], had low or no expression in our samples. Moreover, plasma circulating miRNAs that have been described to be associated with pathological response in Her2+ BC patients (rev in [ 38 ]) such as miR-140-3p, miR-195-5p, miR- 373-3p, and let-7a-3p were negative in our samples.…”
Section: Discussionmentioning
confidence: 79%
“…Few studies have investigated the predictive power of miRNAs in pathological response following NAT in BC. Most of them were only focused on triple negative BC (TNBC) [ 26 , 27 , 28 ], and were evaluated in tissue samples [ 29 ], or enrolled a smaller patient cohort [ 9 , 30 ]. Considering that sEVs miRNAs detected in liquid biopsies represent more accessible and less invasive biomarker sources, our study aims to explore the predictive value of these miRNAs for the pathological response to NAT in BC.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant miRNA expression has already been identified and characterized in a range of biological samples, such as tissues, serum, plasma, CTCs, and exosomes, and their role in the development of new biomarkers for BC has been explored [ 72 ]. Although, few studies have focused on the detection of exo-miRNAs for monitoring the response to therapy in BC [ 73 ], Todorova et al recently investigated the ability of circulating exo-miRNAs to predict pCR in BC patients treated with neoadjuvant chemotherapy (NAC), using next-generation sequencing (NGS) technology [ 67 ]. The authors found that three miRNAs predicted pCR in all analyzed samples (miR-30b, miR-328, and miR-423) before NAC.…”
Section: Monitoring Residual Disease Using Liquid Biopsy Biomarkers D...mentioning
confidence: 99%
“…It is possible to assess treatment response or predict who will not benefit from specific cancer treatments using miRNA expression [ 67 , 99 , 100 , 101 ]. The genes miR21-5p, miR-100-5p, miR-125b-5p, miR-126-3p, miR-375, and miR-424-5p are miRNAs related to BC and the pathways targeted by the drug, dovitinib.…”
Section: Prediction Of Treatment Response and Early Detection Of Relapsementioning
confidence: 99%